Protecting Child Victims in Armed Conflicts: A Critical Look at International Humanitarian Law - Rivanally, Raydiva Tidar; Danial, Danial; Sitamala, Afandi (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2024)
Armed conflicts have severe humanitarian consequences, especially for civilians. Among the most vulnerable are children, who require specific protection under international law. This study examines two critical questions: how the 1949 Geneva Conventions regulate the protection of children in armed conflicts, and whether the protection of children during the Russia-Ukraine conflict aligns with these legal frameworks. Using legal protection theory and humanitarian principles, this normative juridical study analyzes literature and secondary data. The findings reveal that the Geneva Conventions, along with Additional Protocols I and II, explicitly protect children in armed conflicts. However, the study also highlights a breach of these protections in the Russia-Ukraine conflict, where recruitment of minors as soldiers violates international law. This research underscores the urgency of ensuring compliance with international humanitarian law to safeguard children in war.